OPTIMALISASI PELAYANAN HAJI: IMPLEMENTASI SISKOHAT DI KANTOR WILAYAH KEMENTERIAN AGAMA DAERAH ISTIMEWA YOGYAKARTA TAHUN 2020 - Syafii, Ilham (JURNAL MANAJEMEN DAKWAH, 2023)
This research aims to find out how the monitoring system is implemented at the Regional Office of the Ministry of Religion for the Special Region of Yogyakarta regarding the management of data and information on Hajj pilgrim registration, waiting lists, and the process of carrying out the Hajj pilgrimage. This research is field research, using qualitative descriptive analysis. Data collection used primary data with observation, interviews, documentation and secondary data from documents in Siskohat. Data analysis used Miles and Huberman, and data validity testing used source triangulation by checking data obtained from various sources. The results show that the Yogyakarta Regional Office of the Ministry of Religion supervised the registration of Hajj pilgrims using the second-generation Siskohat web-based application on the Sybase ASE (Adaptive Server Edition) database. This form of supervision is carried out by monitoring each Hajj registration process at the Regency/City Ministry of Religion Office regarding existing obstacles as a form of optimizing Hajj services. The source of problems that often occur is the blocking of data on Hajj pilgrims when making initial deposits and the process of handing over portions to prospective pilgrims who are permanently ill or have died as well as incomplete document files. Implementation of Siskohat at the DIY Regional Office of the Ministry of Religion as a monitoring system that has benefits in the monitoring and evaluation process of Hajj implementation in DI Province. Yogyakarta. Supervision is carried out online and in real time so that there is a form of correction and analysis of deviations for Hajj services that can be optimal. When the monitoring process takes place, supervision can be carried out at the same time as Hajj registration.